Pengaruh Self Regulated Learning terhadap Hasil Belajar Siswa - Riani Solikhah; Jaenullah Jaenullah; Dedi Setiawan; Kushendar Kushendar (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2022)
Student achievement in learning outcomes can not be separated from the factors that influence the learning process. In fact, the learning outcomes of students in the Islamic Religious Education subject at SMP Unggulan Darusy Syafa'ah Kotagajah are categorized as lacking. The low student learning outcomes of PAI are thought to be influenced by students' internal factors, namely self-regulation. Self Regulated Learning is able to influence student learning outcomes to increase. This type of research is ex-post facto using a quantitative approach. The population of this research is 117 students and the sample is 38 students. The sampling method used is Proportionate Stratified Random Sampling. Data collection methods with Questionnaire, Test, Observation and Documentation. The data analysis technique is multiple regression analysis. The results of the study show that there is a positive and significant influence between self-regulated learning and student learning outcomes in PAI subjects at SMP Darusy Syafa'ah Kotagajah with the results obtained for a tcount value of 4,390 and for a ttable value of 1,713 or 4,390 > 1,713, then H0 is rejected, H1 is accepted. Thus, it can be said that there is an influence of self-regulated learning on student learning outcomes in PAI lessons at SMP Darusy Syafa'ah Kotagajah.